Corporate Governance in Indian Banking Sector - Gupta, Pushkar (2008)
Corporate Governance has fast emerged as a benchmark for judging corporate excellence in the context of national and international business practices. From guidelines and desirable code of conduct some decade ago, corporate governance is now recognized as a paradigm for improving competitiveness and enhancing efficiency and thus improving investorsÃÂÃÂÃÂÃÂ¢ÃÂÃÂÃÂÃÂÃÂÃÂÃÂÃÂ confidence and accessing capital, both domestic as well as foreign. What is important is that corporate governance has become a dynamic concept and not static one. Banks form a crucial link in a countryÃÂÃÂÃÂÃÂ¢ÃÂÃÂÃÂÃÂÃÂÃÂÃÂÃÂs financial system and their well-being is imperative for the economy. The significant transformation of the banking industry in India is clearly evident from the changes that have occurred in the financial markets, institutions and products. While deregulation has opened up new vistas for banks to augment revenues, it has entailed greater competition and consequently greater risks. Cross-border flows and the entry of new products have significantly influenced the domestic banking sector, forcing banks to adjust the product mix, as also to effect rapid changes in their processes and operations in order to remain competitive in the globalized environment. These developments have facilitated greater choices for consumers who have become more discerning and demanding compelling banks to offer a broader range of products through diverse distribution channels. In such scenario, implementation of good corporate governance practices in banks can ensure them to cope with the changing environment. TodayÃÂÃÂÃÂÃÂ¢ÃÂÃÂÃÂÃÂÃÂÃÂÃÂÃÂs corporate governance means to do everything better and provides for risk assessment, risk cover, early warning systems against failure as well as prompt corrective action. This research examines the practices of corporate governance attributes in banking sector and how they adhere to corporate governance practices. The results of this research indicate the practice of corporate governance is at nascent stage although corporate governance practices by Indian Banking Sector is more than a decade old. Both private and public sector banks are adhering to mandatory requirements of corporate governance attributes as a result it is bringing more transparency and minimizing the chances of fraud and malpractices. However, hope is looming large for the proper implementation of corporate governance principles in Indian Banking Sector.